2022
DOI: 10.1101/2022.07.27.22277602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of BA.5 infection in individuals exposed to prior SARS-CoV-2 variants

Abstract: The SARS-CoV-2 omicron BA.5 subvariant is progressively displacing earlier subvariants, BA.1 and BA.2, in many countries. One possible explanation is the ability of BA.5 to evade immune responses elicited by prior BA.1 and BA.2 infections. The impact of BA.1 infection on the risk of reinfection with BA.5 is a critical issue because adapted vaccines under current clinical development are based on BA.1. We used the national Portuguese COVID-19 registry to analyze the risk of BA.5 infection in individuals without… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…We further showed that the impact of 20% or 40% of unreported infections within the "uninfected" group did not lead to major changes in the calculated risks 1 . We used the national SARS-CoV-2 genetic surveillance database 7 to identify periods when one variant represented >90% of the sample isolates, as also defined and used in other studies 1,3 .…”
Section: Participant Selectionmentioning
confidence: 72%
See 4 more Smart Citations
“…We further showed that the impact of 20% or 40% of unreported infections within the "uninfected" group did not lead to major changes in the calculated risks 1 . We used the national SARS-CoV-2 genetic surveillance database 7 to identify periods when one variant represented >90% of the sample isolates, as also defined and used in other studies 1,3 .…”
Section: Participant Selectionmentioning
confidence: 72%
“…The number of unreported cases was estimated by the National Serological Panel (from November 2021, assaying the presence of antibodies against the SARS-CoV-2 N protein to exclude vaccination seropositivity) to infer that, at that time, there were 29.2% more people who had been infected with SARS-CoV-2 than officially reported 19 . We further showed that the impact of 20% or 40% of unreported infections within the "uninfected" group did not lead to major changes in the calculated risks 1 . We used the national SARS-CoV-2 genetic surveillance database 7 to identify periods when one variant represented >90% of the sample isolates, as also defined and used in other studies 1,3 .…”
Section: Participant Selectionmentioning
confidence: 72%
See 3 more Smart Citations